The Study of Scent Association And Preference Among Youth In Bandung - Kamila, Alivia Puti; Nasution, Reza Ashari (Journal of Business and Management, 2016)
Abstract. Olfactory stimuli, also known as sense of smell, is the part of sensory system that is used for smelling. Scent is the pleasant odor captured by human olfactory system. It is known to add value by the use of fragrance on products. The use of scent by fragrance have been practiced in many industries. Fast moving consumer goods is one of the industry which product uses lot of scents, namely personal care. Product scent is being put into consideration when it comes to choosing personal care product. It is the main purchase driver of personal care product. In order to distinguish itself with others and offer unique selling point, the product must be different and easy to be remembered. This is where perception plays important role by creating cluster of association held in consumer’s mind that is stored in memory. These associations will help marketer to understand the consumer better in order to create a targeted marketing for certain potential market and to generate a scent profile that may be useful for product development. In order to be a favorable scent, it has to be pleasant. However, there has not been any research about whether a pleasant, likeable scent makes consumer want to buy the product. There has not been many research about scent which is why this research will contribute to begin bridging the gap in the real world and the actual association held in consumer’s mind and to find out the relationship between scent likeability and product preference. Therefore, this research was conducted using 5 samples of liquid soap to represent personal care product due to its high intensity of fragrance survey to 101 male and female aged 15-24 years old in Bandung who are divided into two groups based on their age (15-19 years old as teenagers and 20-24 years old as early adult). The respondents were asked to smell the soap first before they fill in the survey. The sample of soap being used are cool, fantasy, fresh, gourmand, and fruit scent. The type of association being asked are personality (symbolic), object, and emotion. The result of this research shows the association of each scent although the result shows little to no difference between two age groups. Charming is the personality that is associated across all scents that are natural based, though fresh does not have any strong personality association to it. These scents generally bring pleasant emotion. The objects associated with the scent come mostly from the item with similar scent to it, object of respondents surrounding, and the source of scent itself These associations help to create scent profile. The relationship between scent likeability and product preference is positive, which means if the scent is liked by consumer then it is also more preferred by consumer.Keywords: olfactory stimuli, scent, association, preference